ANALISIS DAYA DUKUNG DAN INDEKS KESESUAIAN WISATA PANTAI BERAWA CANGGU, KABUPATEN BADUNG, PROVINSI BALI - Sitanggang, Melani; Restu, I Wayan; Kartika, I Wayan Darya (PAPALELE (Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan), 2025)
Berawa Beach is one of the destinations that can attract tourists. The potential tourist attractions of Berawa Beach are beautiful scenery, watching the sunset, taking pictures, relaxing, beach recreation. Berawa Beach is strategically located in Tibubeneng Village, Banjar Berawa, North Kuta District. To access the Berawa Beach tourist attraction, you can go via the Berawa Beach road in Banjar Berawa. Tibubeneng Village consists of 13 Banjar Dinas areas/environments and 3 Traditional Villages. Sustainable development is one strategy that can be applied to maintain environmental sustainability around Berawa Beach, which can be done through research on the Regional Carrying Capacity (DDK) and the Tourism Suitability Index (IKW), considering that both instruments have an important role in indicating the level of feasibility of an area and supporting the planning of tourist destination development. The research was conducted in October - December 2023. The data source for this research is primary data obtained from direct observation and interviews, while secondary data was obtained from literature studies. IKW analysis uses the IKW matrix of recreation categories and tourism suitability assessment classification, while interviews using questionnaires and field observations are used for the Regional Carrying Capacity (DDK). The results of the Regional Carrying Capacity for Sightseeing activities are 8,240 people/day, the Swimming category is 6,994 people/day and for Surfing is 5,349 people/day. The results of the Tourism Suitability Index analysis were obtained at station 1 of 2.3 (Appropriate), at station 2 of 2.5 (Very Appropriate), at station 3 of 2.5 (Very Appropriate).